Effects of the toxic metal zinc on the growth, development, and reproduction of the wolf spider Pardosa laura through its food Drosophila melanogaster. - Zhan, C.; Zhang, Y.; Li, W.; Zhang, S.; Liu, J.; Zhao, Y.; Peng, Y. (Chemosphere, 2023)
In recent years, toxic metal pollution has become a serious problem, and its influence on human society and the ecological environment has become a hot topic for people. Toxic metal pollution is ubiquitous in the environment, and it can affect the growth, development, and reproduction of organisms through food chain transmission. In this study, we used ZnSO4 and set three different Zn concentrations [0 mg/mL (CK), 0.25 mg/mL, and 0.50 mg/mL] to study the enrichment of toxic zinc metal in the wolf spider Pardosa laura through the food chain (medium-Drosophila melanogaster-P. laura) and the effects on the growth, development, and reproduction of D. melanogaster and P. laura. The results of the study showed that the Zn content in D. melanogaster and P. laura significantly increased with the increase of Zn concentration in the culture medium, reflecting the obvious food chain enrichment phenomenon. The inhibitory effect of zinc treatment on the growth, development, and reproduction of D. melanogaster was significant and more pronounced with increasing Zn concentration. The transfer of zinc through the food chain also had a significant inhibitory effect on the growth, development, and reproduction of P. laura. The developmental duration and preoviposition period were significantly prolonged. Moreover, the survival rate, body size, and egg laying amount were significantly reduced. This study will enrich and improve the research on the effects of toxic Zn metal pollution on spiders and provide a theoretical basis for monitoring and evaluating the environmental quality using farmland spiders.